In situ measurements of snow accumulation in the Amundsen Sea Embayment during 2016. Issue 3 (15th March 2018) - Johnson, Joanne S.; O'Donnell, John P.; Thomas, Elizabeth R.
Abstract: Measurements of snow accumulation are critical for reliable prediction of future ice mass loss and hence projections of sea level change. However, there are currently very few published in situ measurements of snow accumulation in the Pine Island–Thwaites glacier catchment of the Amundsen Sea Embayment, and none from low elevation sites west of 100.77° longitude. Here measurements of snow accumulation over an 11 month period in 2016 are reported for six sites in the Pine Island–Thwaites glacier catchment. The average accumulation rates of 0.10±0.01 to 1.26±0.22 m w.e. yr -1 are comparable with those derived from airborne radar for the period 1985–2009, suggesting very high rates of snowfall, particularly in the vicinity of the grounding line.